Shaafa Nursery / Khairul Azhar Hasbi … [et. al.]. - Hasbi, Khairul Azhar; James Jimba Joshua, Agatha; Aminuddin, Hadeeah Najwa; Jori, Nur Azila; Shaharuruddin, Muhd Salaihuddin; Sadinah Abbas, Nurhazirrudin Fadzli (2015)
Shaafa Nursery is a kindergarten where it is actively owned by partnership. Shaafa Nursery will be providing the best service of nursery and baby sitter to our customer with a reasonable price. These days, majority working parents tend to send their children to the nursery and kindergarten during weekdays. With the high demand from the people, we can make our business profitable time after time.